Gamification In Science and Technology Education: A Narrative Review of Implementation Trends and Educator Perspectives - Gunawan Gunawan; Lovy Herayanti; Imran Imran; Fathoroni Fathoroni; Rahmatullah Rahmatullah; Muhammad Hilmy As Shiddiq; Fahmi Yahya (Indonesian Journal of Applied Science and Technology, 2025)
Gamification has emerged as a transformative pedagogical approach in science and technology education. This narrative review explores current implementation trends and educator perspectives by analyzing 28 selected articles published between 2016 and 2024. The study identifies key technological trends, including the integration of Virtual Reality (VR), game-based physics simulations, and Education 4.0 tools. The findings indicate that gamification significantly enhances student motivation, academic achievement, and engagement in complex scientific subjects. Furthermore, the review highlights educator perspectives, revealing that while teachers generally perceive gamification as a potent methodology, its adoption is often hindered by barriers such as limited digital self-efficacy, technical constraints, and the need for specialized training. The synthesis suggests that a successful gamified ecosystem requires a balance between immersive technology and robust pedagogical support. This review provides valuable insights for educators and policymakers seeking to integrate gamified strategies into STEM curricula to foster 21st-century skills.